Reactive Jumps Preserve Skeletal Muscle Structure, Phenotype, and Myofiber Oxidative Capacity in Bed Rest - Blottner, Dieter; Hastermann, Maria; Weber, Robert; Lenz, Regina; Gambara, Guido; Limper, Ulrich; Rittweger, Jörn; Bosutti, Alessandra; Degens, Hans; Salanova, Michele (Frontiers in Physiology, 2020)
Identification of countermeasures able to prevent disuse-induced muscle wasting is crucial to increase performance of crew members during space flight as well as ameliorate patient`s clinical outcome after long immobilization periods. We report on the outcome of short but high impact reactive jumps (JUMP) as countermeasure during 60 days 6° head-down tilt (HDT) bed rest on myofiber size, -type composition, capillarisation and oxidative capacity in tissue biopsies (pre/post/recovery) from the knee extensor vastus lateralis (VL) and deep calf soleus (SOL) muscle of 22 healthy male participants (RSL study 2015-2016, DLR:envihab, Cologne). Bed rest induced a slow-to-fast myofiber shift (type I -> II) with an increased prevalence of hybrid fibers in SOL after bed rest without jumps (CTRL, p = 0.016). In SOL, JUMP countermeasure in bed rest prevented both fast and slow myofiber CSA decrements (p=0.005) in CTR group. In VL, bed rest only induced capillary rarefaction, as reflected by the decrease in local capillary to fiber ratio (LCFR), for both type II (pre vs post/R+10, p= 0.028/0.028) and type I myofibers (pre vs. R+10, p= 0.012), which was not seen in the JUMP group. VO2maxFiber (pL x mm-1 x min-1) calculated from SDH-stained cryosections (OD660nm) showed no significant differences between groups. High-impact jump training in bed rest prevented disuse-induced myofiber atrophy, phenotype transition in SOL, and attenuated capillary rarefaction in the prime knee extensor VL however with little impact on oxidative capacity changes.